Developing a research agenda for understanding the stigma of addictions Part I: Lessons from the Mental Health Stigma Literature. (25th October 2016) - Corrigan, Patrick; Schomerus, Georg; Shuman, Valery; Kraus, Dana; Perlick, Debbie; Harnish, Autumn; Kulesza, Magdalena; Kane‐Willis, Kathleen; Qin, Sang; Smelson, David
Abstract : Background and Objectives: Although advocates and providers identify stigma as a major factor in confounding the recovery of people with SUDs, research on addiction stigma is lacking, especially when compared to the substantive literature examining the stigma of mental illness. Methods: A review of key studies from the stigma literature that yielded empirically supported concepts and methods from the mental health arena was contrasted with the much smaller and mostly descriptive findings from the addiction field. Results: Integration of this information led to Part I of this two part paper, development of a research paradigm seeking to understand phenomena of addiction stigma (eg, stereotypes, prejudice, and discrimination) and its different types (public, self, and label avoidance). Conclusions and Scientific Significance: In Part II paper ( American Journal of Addictions, Vol 26, pages 67–74, this issue), we address how this literature informs a research program meant to develop and evaluate and stigma strategies (eg, education, contact, and protest). Both papers end with recommendations for next steps to jumpstart the addiction stigma portfolio. Here in Part I, we offer one possible list of key research issues for studies attempting to describe or explain addiction stigma. (Am J Addict 2017;26:59–66)